A study on theory and practice of element in compensation through employees Scope International (Malaysia) Sdn. Bhd. / Siti Noor Hasyimah Abd Halim - Abd Halim, Siti Noor Hasyimah (2010)
This case study exploring element of compensation and benefits plan in SCOPE International (M)Sdn Bhd. Here, there are some issues in this study that have been analyze the company practice that contribute in this issues and discussing the gap of compensation and benefits through employees’ expectation and the company perceived. In order to justify on what are the organization implement in providing the compensation and benefits plan to attract their employees, the observation has done for 20 weeks. Through this observation, there are some of issues that related to the employees satisfaction in the compensation and benefits plan provide by the company. On the other words, this study on this issues want to show, what company has done in order to attract and retain their employees, in fact, cover a very wide range of compensation and benefits plan that offer by the company in motivating their employees. All of these issues deeply explained in the report in order to be more clarifying for understanding the element of compensation and benefits plan in the effective way. Therefore, there are some of suggestions that have been explained in enhancing the compensation and benefits plan in the company.